Determination of the angle of repose and coefficient of rolling friction for wood pellets - Madrid, Marcos A.; Fuentes, José María; Ayuga, Francisco; Gallego Vazquez, Eutiquio (My University, 2022)
The determination of the angle of repose for granular materials is indispensable for their handling and the design of containers and technological processing equipment. On the other hand, computational simulations have become an essential tool to understand the micro-behavior of the granular material and to relate it with the macro-behavior. The experimental determination of the angle of repose has a fundamental role when defining the required parameters to perform realistic simulations. However, there is a lack of a standard that allows the reproducibility of the experiments when using granular materials of equivalent spherical radius greater than 2 mm, such as corn, soybeans, wheat and PLA pellets, among others. In particular, a product of growing importance in the global strategy of decarbonization of the economy is biomass pellets, whose handling operations are one of the main components for the total cost of pellets supplied to the final user. In the present work, with the aim of determining the rolling friction coefficient, the variations in the angle of repose with the drop height for biomass pellets were studied both experimentally and with simulations, and an optimal procedure for its determination was found. Then, a calibration of the coefficient of rolling friction was performed through computational simulations using the discrete element method. The accuracy of the model under different configurations was checked.
Keywords: Numerical simulations; Angle of repose; Wood pellets; Biomass; Coefficient of rolling friction; DEM; Simulation